Urgensi Leadership Dalam Manajemen Pendidikan Islam - Irfan Kuncoro (Thawalib: Jurnal Kependidikan Islam, 2021)
This article discusses the urgency of leadership with must-have skills and management capabilities in Islamic education. This article uses a qualitative descriptive analysis of the object of discussion by utilizing reference sources for related themes and using library research methods. This article argues that leadership is very much needed in Islamic educational institutions today, where the leadership in question must have visionary skills, personal risk, sensitivity, broad insight, charisma, communicative, exemplary, and not egotistical. Furthermore, with good management where management is meant is the art of completing projects, activities with an epic collaboration and understanding what you want to do and then doing it in an effective and efficient way. Therefore, this article offers idealistic leadership with good Islamic education management in shaping the golden generation in the future.